Profil Kemampuan Literasi Numerasi, Digital dan Budaya Siswa Kelas IV UPTD SD Negeri Riominsi - Rasdiyanti, Yohana; Wangge, Maria Carmelita Tali; Wewe, Melkior; Bela, Maria Editha; Bhoke, Wilibaldus (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to determine: 1) the profile of the numeracy literacy ability of the fourth grade students of UPTD SD Negeri Riominsi, 2) the profile of the digital literacy ability of the fourth graders of the UPTD SD Negeri Riominsi, 3) the profile of the cultural literacy ability of the fourth graders of the UPTD SD Negeri Riominsi. The results showed that the fourth grade students' numeracy literacy skills were still in the low category with a percentage of 25%. For the digital literacy ability of fourth graders is also still in the low category. This is obtained from data from interviews and observations made by researchers, namely the digital literacy ability of fourth graders as much as 25%. Meanwhile, for cultural literacy skills, when viewed from the data from interviews and observations made by researchers, as much as 25%, this shows that the cultural literacy skills of fourth graders are still in the low category. Based on the results of data analysis there is an increase from 25% to 50%.